1998
DOI: 10.1093/glycob/8.7.637
|View full text |Cite
|
Sign up to set email alerts
|

Glycosphingolipid expression in pig aorta: Identification of possible target antigens for human natural antibodies

Abstract: Total non-acid glycosphingolipids were isolated from the aortas of more than 80 pigs. The glycolipids were separated by HPLC, analysed by thin-layer chromatography, and tested for reactivity with monoclonal anti-blood group antibodies. The fractions were structurally characterized by NMR spectroscopy and mass spectrometry. Reactivity with both antiblood group A and H antibodies was seen. The major glycosphingolipid constituents were globotriand globotetraosylceramides and blood group H pentaglycosylceramides b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…Concerning glyco-antigens on the pig cell, before the a-Gal was knocked out, Bouhors et al, in their analysis of glycosphingolipids from the pig kidney in 1997, reported that the Gala1-3Lew x is a new epitope capable of being recognized by the human natural antibody (NA) [18]. Using a similar method of analysis, Hallberg et al also indicated that Gal a1-3Lew x and Gala1-3nLc4(neolactotetraosylceramid) were important targets for human NA [19]. In addition, quite recently, Kim et al reported that NeuGc-Gal-GlcNAc and Gala1-3Lew x were novel antigens, as evidenced by a structural analysis of N-glycans from the miniature pig kidney, using MALDI-TOF/MS and MS/MS [20].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning glyco-antigens on the pig cell, before the a-Gal was knocked out, Bouhors et al, in their analysis of glycosphingolipids from the pig kidney in 1997, reported that the Gala1-3Lew x is a new epitope capable of being recognized by the human natural antibody (NA) [18]. Using a similar method of analysis, Hallberg et al also indicated that Gal a1-3Lew x and Gala1-3nLc4(neolactotetraosylceramid) were important targets for human NA [19]. In addition, quite recently, Kim et al reported that NeuGc-Gal-GlcNAc and Gala1-3Lew x were novel antigens, as evidenced by a structural analysis of N-glycans from the miniature pig kidney, using MALDI-TOF/MS and MS/MS [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, concerning Gala1-3Lew x , in 1997, Bouhors et al already reported it as a new epitope for the human natural antibody in their analysis of glycosphingolipids from the pig kidney [146]. Hallberg et al also indicated that Gal a1-3Lew x and Gala1-3nLc4 were important targets for the human natural antibody [147].…”
Section: The Other Non-gal Antigensmentioning
confidence: 99%
“…Since permethylation also improves the stability and sensitivity of the charged glycans, especially sialic acid, neutral and sialylated glycans were observed in positive mode as [M 1 Na] 1 ions. The identified sialylated Nglycan structures are listed in Table 1 [26,27] analyzed glycosphingolipid expressed in pig kidney and aorta and firstly reported the expression of Gala1,3Lewis x as well as a-Gal-terminated GSL in pig organ. However, the Gala1,3Lewis x epitopes have not been reported in N-glycans from pig organs.…”
Section: Ms-profiling Of Permethylated N-glycans From Pig Kidney Membmentioning
confidence: 99%